1973
DOI: 10.1677/joe.0.0560309
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Uterine Blood Vessels in the Refractory State of the Uterine Stroma Which Follows Oestrogen Stimulation in Progesterone-Treated Mice

Abstract: Increases in uterine capillary permeability after the injection of oestradiol into spayed mice, appeared to be caused by the development of vascular fenestrations and not by the separation of adjoined endothelial cells. Progesterone did not prevent the uterine weight, oedema and vascular responses to the first of two injections of oestradiol but inhibited those to the second. It was concluded that the failure of repeated oestrogen-treatment to produce uterine oedema in progesterone-treated mice resulted from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1975
1975
1993
1993

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 13 publications
(22 reference statements)
1
12
0
Order By: Relevance
“…Furthermore, there is a need for rapid expansion of the epithelial sheet to accommodate placental fold formation. It is of interest that death of uterine epithelial cells is reduced or prevented by estradiol treatment in the mouse (Martin et al, 1973(Martin et al, , 1976Finn and Publicover, 1981), hamster (Sandow et al, 19791, and rabbit (Conti et al, 1984). Local concentrations of estradiol at sites of attachment would be elevated during placental establishment in the pig, and its local action could explain a regional reduction in cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a need for rapid expansion of the epithelial sheet to accommodate placental fold formation. It is of interest that death of uterine epithelial cells is reduced or prevented by estradiol treatment in the mouse (Martin et al, 1973(Martin et al, , 1976Finn and Publicover, 1981), hamster (Sandow et al, 19791, and rabbit (Conti et al, 1984). Local concentrations of estradiol at sites of attachment would be elevated during placental establishment in the pig, and its local action could explain a regional reduction in cell death.…”
Section: Discussionmentioning
confidence: 99%
“…On the morning of day 6 of pregnancy, 0.8 ml of a 1:1 mixture of Gd-DTPA and Evans blue was injected into a tail vein as described above. Animals were killed by decapitation 15 min later, and uteri were removed and imaged as described. Statistical analysis.…”
Section: Animalsmentioning
confidence: 99%
“…We have now used this technology to investigate uterine vascular changes associated with both ovoimplantation and artificial decidualization in rats. Studies involving electron microscopy have suggested that the endothelial layer of endometrial blood vessels can present a formidable barrier to the passage of blood-borne molecules in certain endocrine states (15) and in uterine tissue outside the implantation sites of pregnant rats (16). Therefore, we have also measured the uterine volume of distribution of ls3Gd-DTPA in both decidualizing and nondecidualizing…”
Section: Introductionmentioning
confidence: 99%
“…In ovariectomized, progesterone-treated and metoestrousdioestrous mice the endometrial endothelium is continuous with few or no fenestrations and the intercellular clefts between adjoining cells are sealed by tight junctions (Castillo-Jessen & GonzalezAngulo, 1973;Martin et al, 1973). Furthermore, by as late as 6 h after intravenous injection of horseradish peroxidase (M, 40 000; Einstein-Stokes radius (ESR) 3.0 nm) to metoestrousdioestrous mice, no reaction product is observed outside the vascular lumen (Castillo-Jessen & Gonzalez-Angulo, 1973), demonstrating a marked impermeability of these junctions.…”
Section: Permeability and Transport Properties Of Uterine Endotheliummentioning
confidence: 99%
“…Furthermore, by as late as 6 h after intravenous injection of horseradish peroxidase (M, 40 000; Einstein-Stokes radius (ESR) 3.0 nm) to metoestrousdioestrous mice, no reaction product is observed outside the vascular lumen (Castillo-Jessen & Gonzalez-Angulo, 1973), demonstrating a marked impermeability of these junctions. By contrast, in oestrogen-treated mice and rats the endothelium is fenestrated to a greater extent (Martin et al, 1973) and intercellular gaps are frequently observed (Ham et al, 1970). Furthermore, these intercellular endothelial clefts in pro-oestrous-oestrous mice are clearly permeable to horseradish peroxidase since enzyme activity is apparent in vascular lumen, intercellular clefts and perivascular space as early as 1 min after intravenous injection (Castillo-Jessen & Gonzalez-Angulo, 1973).…”
Section: Permeability and Transport Properties Of Uterine Endotheliummentioning
confidence: 99%